PEMBENIHAN IKAN KERAPU TIKUS (Cromileptes altivelis) DI INSTALASI PEMBENIHAN BALAI BUDIDAYA AIR PAYAU (BBAP) SITUBONDO, JAWA TIMUR - Dimas Galang Prakosa; Wahyu Endra Kusuma; Sus Setyo Pramujo (Samakia : Jurnal Ilmu Perikanan, 2013)
Humpback grouper (Cromileptes altivelis) is one of the leading commodity food fish seawater is prospective to be developed because it has a high protein content is about 30-35% and the cholesterol content is quite low, around 3%. Hatchery of Cromileptes altivelis held in the Hall of Brackish Water Aquaculture (BBAP) Situbondo Regency East Java Province. Activities undertaken is the selection and preparation of the parent, pond preparation, water quality measurements, spawning, hatching eggs, larva, feeding, harvesting of pest eradication. The feeding is done adlibitum. During the course, identification of problems existing in Humpback grouper hatchery did not find any problems, just may need to be re-examined on elevating hatchability while still larvae.